On the Production of Subjectivity - O'Sullivan, S. author. aut Link
XV, 300 p.
Keywords: This book offers a series of critical commentaries on, and forced encounters between, different thinkers. At stake in this philosophical and psychoanalytical enquiry is the drawing of a series of diagrams of the finite/infinite relation, and the mapping out of the contours for a speculative and pragmatic production of subjectivity.